2022
DOI: 10.1038/s41598-022-22636-9
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of decreased estimated glomerular filtration rate using liver fibrosis markers: a renal biopsy-based study

Abstract: Non-alcoholic fatty liver disease is the most common chronic liver disease and is associated with chronic kidney disease. The fibrosis-4 index and non-alcoholic fatty liver disease score are widely used as non-invasive diagnostic methods for non-alcoholic fatty liver disease. However, the relationship between these markers and specific renal histopathologies in chronic kidney disease remain unclear. This study included 179 patients aged between 16 and 80 years who underwent renal biopsy. We examined the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Inflammation and oxidative stress play important roles in organ damage progression (18)(19)(20) because they promote fibrosis (21,22). Nuclear factor-kappa-B (NF-ĸB) stimulates cytokine expression via reactive oxygen species and PKCβ.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and oxidative stress play important roles in organ damage progression (18)(19)(20) because they promote fibrosis (21,22). Nuclear factor-kappa-B (NF-ĸB) stimulates cytokine expression via reactive oxygen species and PKCβ.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and oxidative stress play essential roles in DKD initiation, development, and progression [ 27 ]. In addition, they can promote renal fibrosis [ 17 , 28 ]. Finerenone has stronger anti-fibrotic activity than eplerenone.…”
Section: Discussionmentioning
confidence: 99%
“…UPCR was calculated by dividing the level of protein (mg/dL) in a spot urine test by the creatine level (mg/dL). The eGFR of each patient was calculated using the formula by isotope dilution mass spectrometry (IDMS) traceable 4-variable MDRD (Modification of Diet in Renal Disease) (IDMS-MDRD Study formula) with the 3-variable Japanese equation: 194 × serum creatinine - 1.094 × age - 0.287 × 0.739 (if female) [ [15] , [16] , [17] , [18] ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the liver fibrosis scores (i.e., LS, NFS, and FIB-4, as estimations of hepatic fibrosis) were also higher in those with mild or moderate CKD than in those without CKD in the present study. The kidney biopsy-based study [ 35 ] showed that the liver fibrosis markers FIB-4 and NFS were negatively correlated with the eGFR in nephrosclerosis and IgA nephropathy. This result suggests that it is important to identify individuals with NAFLD early in the course of their disease and provide appropriate treatment and care to prevent negative outcomes.…”
Section: Discussionmentioning
confidence: 99%